Prevalence and types of anemia among children at a tertiary care hospital - Reddy A., Bhaskar; Chandra, V. Sharath; Eluzai, Zion (International Journal of Contemporary Pediatrics, 2018)
Background: The anemic children tend to have average or below average academic performance due to effect of anemia on cognitive and behavioral aspect of the child. The objective of the study is to study prevalence and types of anemia among children at a tertiary care hospital. Methods: A total of 6000 patients attended the outpatient department of the SVS hospital, Mahabubnagar during the study period. Out of them 1237 patients were pediatric patients who attended the pediatric outpatient department. Among these 1237 children, 823 children were found anemic. Among these 823 anemic children, 100 were randomly included in the present study for further investigations. Thus, final sample size of the present study was randomly selected 100 anemic children. Results: The incidence of anemia was found to be very high i.e. 66.5%. It was found that the prevalence of anemia was 60.9% among females compared to only 39.1% among male children. The prevalence of anemia was significantly higher in females compared to males. In both males and females, the iron deficiency anemia was the most common type of anemia found in the present study. Maximum prevalence of iron deficiency anemia was seen in 1-5 years of age in females. Maximum prevalence of iron deficiency anemia was seen in 1-5 years of age in males. The most common grade of anemia was moderate grade followed by mild. Conclusions: Iron deficiency anemia is more prevalent in female children. In males also, it is not found to be very low. Its prevalence in males is also noticeable.